Rubio de Francia’s Extrapolation Theorem in Grand Lebesgue Spaces - Makharadze, Dali; Meskhi, Alexander (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
In this note, we present multilinear Rubio de Francia′s extrapolation theorem in grand Lebesgue spaces. The mapping properties of bilinear maximal operators in harmonic analysis are also discussed.